THE USE OF TAXONOMIC CLUSTERING MECHANISMS IN THE PROCESS OF PSYCHOLOGICAL DIAGNOSTICS OF SOCIAL SUCCESS OF YOUNGER SCHOOLCHILDREN - Stryzhak, Alla; Stryzhak, Oleksandr (PSYCHOLOGICAL JOURNAL, 2023)
The objective of this article is to explore the correlation between specific psychological profiles, which characterize the expressive and communicative abilities of primary school-aged children in narrative formats, and their social success during interactions. The clustering of schoolchildren’s social success is achieved through the use of growing pyramidal networks, which structurally represent the operational environment of their activities during interactions. The input data for the clustering process consist of values obtained from psychological profiles, evaluated using appropriate scales in the testing of schoolchildren according to specific methods. The clustering procedure identifies forty psychological profiles that reflect the dynamics of their interaction in narrative formats and their corresponding levels of social success. Taxonomic clustering of the test results of junior schoolchildren reveals stable groups of interactions among them.